AN ANALYSIS OF MEASUREMENT CONTACT RESISTANCE AND GROUND RESISTANCE IN THE POWER BREAKER (PMT) - Steven Riki Daniel; Hermansyah Alam (Sean Institute, 2023)
In this paper discussed about operates in all sectors regarding electricity such as generation, transmission and distribution, maintenance of installation facilities plays an important role in supporting the quality and reliability of electricity supply to consumers. Maintenance of installation facilities is one of the activity processes that aims to maintain the condition of electric power equipment, so that in operation the equipment can always function properly according to the standards set by PT. PLN (Persero). Based on IEV (International Electrotechnical Vocabulary) 441-14-20 it is stated that a Circuit Breaker (CB) or Power Breaker (PMT) is a mechanical switch / switching equipment, capable of closing, flow (within a certain period of time) and break the load current in specific abnormal/interference conditions such as short circuit conditions. As the duration of the operation of the circuit breaker (PMT), it is very necessary to check and measure one of the contact resistance.